Additional court player: possibilities for tactical variations and their implications for the handball training process - João Paulo Torres Di Gilio; Renato Francisco Rodrigues Marques; Rafael Pombo Menezes (E-balonmano.com: Revista de Ciencias del Deporte, 2024)
Handball game passed by normative changes in 2016, and some influenced the use of the additional court player (ACP), both related to organizational, strategic, tactical, and technical issues. This study aimed to analyze, from the speeches of Brazilian handball coaches, the influence of ACP on handball training process after 2016. Seven coaches were interviewed, who have already been classified among the top four clubs in the Brazilian national men and women leagues and/or who participated in the technical staff of the Brazilian national teams (men and/or women). Data were thematically analyzed. The 2016 normative change raised new handball tactical landscapes, as the coaches developed changings on offensive and defensive actions using and playing against ACP.